A facile and green preparation of nanosilica-supported antioxidant and its reinforcement and antioxidation effect on styrene-butadiene rubber. Issue 3 (2nd April 2016) - Hu, Dechao; Jia, Zhixin; Zhong, Bangchao; Chen, Yongjun; Luo, Yuanfang; Jia, Demin
ABSTRACT: A novel solid-phase method has been proposed to prepare a nanosilica-supported antioxidant by the reaction of nanosilica with 2-mercaptobenzimidazole (MB) and silane coupling agent γ-chloropropyltriethoxysilane. Fourier transform-infrared spectroscopy and other characterization methods confirmed that MB was chemically bonded onto the surface of nanosilica. Silica-s-MB was homogeneously dispersed in a styrene-butadiene rubber (SBR) matrix with strong filler-rubber interaction, leading to enhanced mechanical performance of SBR/silica-s-MB composites compared with SBR/m-silica composites. Based on the results of thermo-oxidation testing of SBR/silica-s-MB and SBR/m-silica/MB composites containing equivalent antioxidant component, silica-s-MB showed better antioxidative efficiency than the corresponding low-molecular-weight MB owing to its lower migration and volatility at high temperature.